Microfilaria in fine-needle aspiration cytology of renal mass – an unusual site: A rare case report - Majed Momin; Abhijeet Ingle; S Sandeep (BLDE University Journal of Health Sciences, 2018)
In tropical countries like India, filariasis is one among the major public health problems. Most commonly (90%) cases of lymphatic filariasis caused by wuchereria bancrofti, and rest (10%) cases by Brugia malayi. In India, filariasis is transmitted by the bite of culex or mansonia mosquito species. The diagnostic method of choice in filariasis is the detection of microfilaria in peripheral blood film examinations. Microfilaria was incidentally detected in fine-needle aspiration cytology (FNAC) smears from different tissues, organs, and serous cavities. However, the presence of a filarial worm in renal mass aspirate is unusual, and no literature has been published with best of our knowledge. We report a case in which ultrasound-guided FNAC renal mass revealed the presence of microfilaria in the background of renal cell carcinoma cells.